Benefit of particle therapy in re-irradiation of head and neck patients. Results of a multicentric in silico ROCOCO trial. Issue 3 (December 2016) - Eekers, Daniëlle B.P.; Roelofs, Erik; Jelen, Urszula; Kirk, Maura; Granzier, Marlies; Ammazzalorso, Filippo; Ahn, Peter H.; Janssens, Geert O.R.J.; Hoebers, Frank J.P.; Friedmann, Tobias; Solberg, Timothy; Walsh, Sean; et al.
Abstract: Background and Purpose: In this multicentric in silico trial we compared photon, proton, and carbon-ion radiotherapy plans for re-irradiation of patients with squamous cell carcinoma of the head and neck (HNSCC) regarding dose to tumour and doses to surrounding organs at risk (OARs). Material and Methods: Twenty-five HNSCC patients with a second new or recurrent cancer after previous irradiation (70 Gy) were included. Intensity-modulated proton therapy (IMPT) and ion therapy (IMIT) re-irradiation plans to a second subsequent dose of 70 Gy were compared to photon therapy delivered with volumetric modulated arc therapy (VMAT). Results: When comparing IMIT and IMPT to VMAT, the mean dose to all investigated 22 OARs was significantly reduced for IMIT and to 15 out of 22 OARs (68%) using IMPT. The maximum dose to 2% volume ( D 2 ) of the brainstem and spinal cord were significantly reduced using IMPT and IMIT compared to VMAT. The data are available onwww.cancerdata.org . Conclusions: In this ROCOCO in silico trial, a reduction in mean dose to OARs was achieved using particle therapy compared to photons in the re-irradiation of HNSCC. There was a dosimetric benefit favouring carbon-ions above proton therapy. These dose reductions may potentially translate into lower severe complication rates related to the re-irradiation.